School Management System (SPS): factors affecting school effectiveness - Wan Mahmud, Wan Marfazila; Ab.Jalil, Habibah (Elite Scientific Publications, 2024)
Nowadays, information management system plays a vital role in organizations. Schools are among the organizations that utilize an information management system in their operation. The purpose of this research is to predict the influence of the School Management System’s (SPS) usability, acceptance, and changes toward school effectiveness, predict the gender of teachers responsible for moderating the influence of usability, acceptance, and change toward school effectiveness, and build a prediction model suitable for the usability, acceptance, and changes in the management of the SPS, with school effectiveness in mind. This research was done for four districts which had been chosen at random, according to the states and zones in Peninsular Malaysia including Central Zone (Petaling Perdana district, Selangor), North Zone (North East district, Penang), East Zone (Kota Bahru district, Kelantan) and South district (Johor Bahru district, Johor). Descriptive research design and correlation through survey were used in this research. Survey questionnaires were distributed to 420 teachers, who were the samples of this research. Samples are chosen by the stratified random sampling technique and random sampling. Five constructs involved in SPS usability include SPS quality, SPS information quality, SPS quality service, SPS satisfaction, and SPS usage. For SPS acceptance, there are four constructs involved namely performance expectation, effort expectation, social influence, and condition of facility. For SPS change management, there are five constructs involved - awareness, eagerness, knowledge, ability, and reinforcement. Data was analyzed descriptively, and inference was made using IBM SPSS and AMOS version 22.0. Structural Equation Modelling (SEM) was used for the hypothesis testing. The result of the analysis shows that the SPS usability, SPS acceptance, and SPS change management towards school effectiveness reach a good correlation based on the value (RMSEA=.046, p=.000, CFI=.903, IFI=.903, TLI=.900 dan CMIN/df=1.815). Variables of SPS usability, SPS acceptance, and SPS change management holistically contribute 64% toward school effectiveness. Variables SPS usability and SPS acceptance are significantly related to school effectiveness. However, it was discovered that gender is not a moderator for the variables of SPS usability, SPS acceptance, and SPS change management toward school effectiveness. There are recommendations that the SPS change management should be encouraged to help teachers prepare and understand the implementation of SPS to increase school effectiveness and school management. This is important to ensure that teachers can effectively accept any change taking place in any new change of policy. For the SPS usability aspect, researchers suggest that the system applied at school be given high priority and consideration by the policymakers to ensure that the system’s application in school is effective and beneficial to the school. This is to ensure a more systematic school governance, yielded from this effort of improving the school management system (SPS).